APPRENTISSAGE DE JEU DE MANGULA (NDEVA) ET SPECIFICITE D'ERREURS CHEZ LES JEUNES NANDE (NORD-KIVU) - Prof MATSORO Amédée, (IJRDO- Journal of Educational Research, 2024)
Mangula games, as considered in this article, present themselves as an instrument allowing us to understand the cognitive aspect of young adolescents, both in school and out of school. The fundamental hypothesis concerns the comparison of performances between these two groups. Young people who are not in school take less time to learn compared to young people in school.